COMPARATIVE TEXTUAL STUDY OF I SAMUEL 2:12-17 AND LUKE 3:18-20 AND THE RELEVANCE FOR CONTEMPORARY CHRISTIAN FAMILY EDUCATION - Subaedah Luma; Ryanto Adilang (Didaskalia: Jurnal Pendidikan Agama Kristen, 2025)
The dilemma between strict and gentle education patterns is still trapped in a never-ending turmoil. In Indonesia itself, this can still be seen clearly. Through the decision of the Governor of West Java to send naughty children to be trained in military barracks, many have reacted and spoken up. Some agree with the breakthrough, but some oppose it on the grounds that the action is not good for the child's psychology. This study uses a qualitative research method with a comparative approach. This study compares two priestly families in the Bible recorded in the book of Samuel and the Gospel of Luke. To analyze the text, the hermeneutic method of Thematic Criticism is used. The main theory underlying this study is Albert Bandura's Social Learning Theory which is used to highlight the influence of the environment on children's learning. This research is expected to contribute to determining the right educational pattern, especially the education of today's Christian families. From this research, it is also expected that an understanding will emerge about how the Bible describes and elaborates on the fact that the social environment can influence the education of children in Christian families.